2010
DOI: 10.2140/jomms.2009.4.1689
|View full text |Cite
|
Sign up to set email alerts
|

Moment Lyapunov exponents and stochastic stability for two coupled oscillators

Abstract: The Lyapunov exponent and moment Lyapunov exponent of two degree-of-freedom linear systems subjected to white noise parametric excitation are investigated. Through a perturbation method we obtain the explicit asymptotic expressions for these exponents in the presence of low intensity noise. The Lyapunov exponent and moment Lyapunov exponents are important characteristics for determining the almostsure and moment stability of a stochastic dynamical system. As an example, we study the almost-sure and moment stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…and after introdusing suposed expressions (64) for solutions in the system of partial fractional order differential equations ( 63), we obtain system of ordinary fractional order differential equations along eigen time functions T k nm ð Þ ðtÞ, k ¼ 1; 2; 3, n; m ¼ 1; 2; 3; 4 . .…”
Section: Governing Partial Fractional Order Differential Equations Of a Hybrid Multi Deformable Beam System Transversal Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…and after introdusing suposed expressions (64) for solutions in the system of partial fractional order differential equations ( 63), we obtain system of ordinary fractional order differential equations along eigen time functions T k nm ð Þ ðtÞ, k ¼ 1; 2; 3, n; m ¼ 1; 2; 3; 4 . .…”
Section: Governing Partial Fractional Order Differential Equations Of a Hybrid Multi Deformable Beam System Transversal Oscillationsmentioning
confidence: 99%
“…12,13,20,24,27,31,33,35,[39][40][41] In Hedrih (Stevanovi c) and Simonovi c [42][43][44][45][46][47][48][49][50][51] published in period in 2008-2013, and late published Simonovi c [52][53][54] as well as in monographs published by Kluwer and Springer and other contributions of author and coauthors to linear and nonlinear dynamics of deformable bodies (rods, beams, plates, moving strips) can be classified as systems of coupled subsystems and deformable bodies. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] After the first published scientific papers by Hedrih (Stevanovi c) K.R. in the newly opened field of coupled deformable bodies and the dynamics of hybrid systems of complex structures, Hedrih (Stevanovi c) K.R.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the ``periodic windows" or intervals of the largest Lyapunov exponent beyond the onset of chaotic motion are gradually diminished when the intensity of bounded noise is increased. Another approach on the two degree-of-freedom linear systems [16] was presented and better response of stability from Lyapunov and moment Lyapunov were recorded. Therefore, so far the disturbance due to colored noise has not been focused.…”
Section: Cdsr 116-2mentioning
confidence: 99%
“…For example, Sri Namachchivaya and Van Roessel [27] studied the moment Lyapunov exponents of two-degrees-of-freedom coupled elastic oscillators under real noise excitation by combining an asymptotic approximation for the moment Lyapunov exponents. Kozić and his associates [28][29][30] developed the first-order perturbation approach to obtain weak noise expansion of moment Lyapunov exponents and Lyapunov exponents for a stochastically coupled doublebeam system and Timoshenko beam system, respectively. Subsequently, Stojanović and Petković [31] used a perturbation method to study the moment Lyapunov exponents and the Lyapunov exponents of the three elastically connected Euler beams.…”
Section: Introductionmentioning
confidence: 99%